Partition Behavior of Lipophilic Compounds Incorporated in Submicron Emulsion: Effects of Physicochemical Properties, Concentrations and Incorporation Methods - Warisada Sila-on (Chulalongkorn University, 2012)
Thesis (Ph.D.)--Chulalongkorn University, 2003